2016
DOI: 10.1007/s10591-016-9378-6
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Family Therapy in Residential Settings

Abstract: This article provides an overview of the history of family involvement in residential treatment as well as a synthesis of the research showing family-centered interventions and outcomes for youth in residential settings. There are many methods for engaging families in residential treatment that are discussed in the literature; however, there is a significant gap as the field has not yet identified specific family therapy approaches that demonstrate efficacy in working with youth and their families in this part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…EBPs included family therapy, case management, peer support, family psychoeducation, and telehealth. First, family therapy is widely used in RT to build relationships among family members and improve family function (Merritts, 2016). Effective family therapy in RT is essential to the health and well-being of children and their families (Sunseri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…EBPs included family therapy, case management, peer support, family psychoeducation, and telehealth. First, family therapy is widely used in RT to build relationships among family members and improve family function (Merritts, 2016). Effective family therapy in RT is essential to the health and well-being of children and their families (Sunseri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To avoid further disruption of family relationships, it is often combined with systemic interventions. Because family functioning is predictive of adolescent outcomes post-discharge (Merritts, 2016), and because studies have found that residential programs offering systemic treatment had better outcomes than programs offering only individual treatment (Gorske et al, 2003), this study focuses on adolescent and familial outcomes of families who receive secure residential youth care combined with systemic interventions in the Netherlands.…”
Section: Systemic Interventionsmentioning
confidence: 99%
“…Parental involvement in residential youth care has been shown to improve family relationships and treatment engagement, and to lead to reductions in parenting problems and adolescent behavior problems (Huefner et al, 2015;Merritts, 2016;Preyde et al, 2011). Greater parental involvement has the potential to improve bonding and relationships between parents and adolescents.…”
Section: Systemic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to study what activities of FCP work for whom, but family involvement practices in youth treatment have not received much research attention (Affronti & Levison‐Johnson, 2009; Merritts, 2016). Partly due to the unclarities in operationalizations of FCP, knowledge of the effectiveness of FCP remains limited.…”
Section: Introductionmentioning
confidence: 99%